Magnetoelectric coefficient in strontium ruthenate buffered lanthanum modified bismuth ferrite thin films grown by chemical method - Simões, Alexandre Zirpoli; Garcia, Filiberto Gonzalez; Moura, Francisco [UNESP] (American Scientific Publishers, 2009)
This paper focuses on the magnetoelectric coupling (ME) at room temperature in lanthanum modified bismuth ferrite thin film (BLFO) deposited on SrRuO 3-buffered Pt/TiO 2/SiO 2/Si(100) substrates by the soft chemical method. BLFO film was coherently grown at a temperature of 500 °C. The magnetoelectric coefficient measurement was performed to evidence magnetoelectric coupling behavior. Room temperature magnetic coercive field indicates that the film is magnetically soft. The maximum magnetoelectric coefficient in the longitudinal direction was close to 12 V/cmOe. Dielectric permittivity and dielectric loss demonstrated only slight dispersion with frequency due the less two-dimensional stress in the plane of the film. Polarization reversal was investigated by applying dc voltage through a conductive tip during the area scanning. We observed that various types of domain behavior such as 71 ° and 180° domain switching, and pinned domain formation occurred. Copyright © 2009 American Scientific Publishers All rights reserved.
Keywords: Ceramics; Chemical syntheses; Dieletric response; Multiferroics; Piezoelectric force microscopy; Piezoelectricity; Bismuth ferrites; Chemical method; Chemical synthesis; Coercive field; DC voltage; Dielectric permittivities; Domain behavior; Domain formation; Domain switchings; Longitudinal direction; Magnetoelectric coefficients; Magnetoelectric couplings; Polarization reversals; Room temperature; Si (100) substrate; Soft chemical method; Strontium ruthenates; Two-dimensional stress; Bismuth; Ceramic materials; Crystallography; Dielectric losses; Electric force microscopy; Electromagnetic coupling; Ferrite; Lanthanum; Lanthanum alloys; Magnetic domains; Piezoelectric devices; Silicon compounds; Strontium; Synthesis (chemical); Thin films; Composite micromechanics